The Influence of Work Behavior and Workload on Employee Performance at PT Air Minum Bandarmasih (PERSERODA) Banjarmasin - Desy Nuryanti; Syahrani Syahrani; FA Sanjaya (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the importance of understanding factors influencing employee performance, particularly at PT Air Minum Bandarmasih (PERSERODA) Banjarmasin. The study aims to analyze the effects of work behavior and workload on employee performance, both partially and simultaneously. This quantitative research employs a survey design with a population of 380 employees and a sample of 79 respondents selected using random sampling based on Slovin's formula. The data were analyzed using validity and reliability tests, classical assumption tests, linearity tests, multiple linear regression analysis, and hypothesis testing. The results reveal that work behavior and workload significantly affect employee performance, both individually and simultaneously. Positive work behavior enhances employee motivation, while a proportional workload supports employees in developing their potential. The implications of this study highlight the importance of organizational management in fostering productive work behavior and effectively managing workload to sustainably improve employee performance.